miR-200 family controls late steps of postnatal forebrain neurogenesis via Zeb2 inhibition - Beclin, Christophe (Nature Publishing Group, 2016)
During neurogenesis, generation, migration and integration of the correct numbers of each neuron sub-type depends on complex molecular interactions in space and time. MicroRNAs represent a key control level allowing the flexibility and stability needed for this process. Insight into the role of this regulatory pathway in the brain is still limited. We performed a sequential experimental approach using postnatal olfactory bulb neurogenesis in mice, starting from global expression analyses to the investigation of functional interactions between defined microRNAs and their targets. Deep sequencing of small RNAs extracted from defined compartments of the postnatal neurogenic system demonstrated that the miR-200 family is specifically induced during late neuronal differentiation stages. Using in vivo strategies we interfered with the entire miR-200 family in loss- and gain-of-function settings, showing a role of miR-200 in neuronal maturation. This function is mediated by targeting the transcription factor Zeb2. Interestingly, so far functional interaction between miR-200 and Zeb2 has been exclusively reported in cancer or cultured stem cells. Our data demonstrate that this regulatory interaction is also active during normal neurogenesis.